PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP PENINGKATAN Vo2max PEMAIN SEPAK BOLA EKACITA FC. - Lalu Sapta Wijaya Kusuma (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
Club football Ekacita FC Masbagik is one of the clubs in the northern part of Masbagik most of the players are from the children of North Masbagik Masongribe Village with head coach namely Lalu Hulfian. At the time of the match or a friendly match between other clubs in the district of East Lombok, one of them is Kanjeng FC, There are several problems that find them are: 1). The many players who do passing are not accurate, 2). Flicking the ball to the front of the goal becomes inaccurate, 3). Shooting on goal becomes improperly targeted, and 4). the main thing in this research is the players quickly feel fatigue while playing, this is all due to the low ability of VO2 Max players. So according to our analysis it is not a good cause the players perform various techniques or tactics applied by the coach himself. Problem formulation in this research is whether there is influence of Circuit Training exercise to increase VO2 Max soccer player FC Ekacita? The general objective in this research is to know whether or not the effect of the Circuit Training exercise on the improvement of VO2 Max soccer player FC Ekacita ". The design of this research is one group pre-test and post-test design. The sample in this study amounted to 20 people. The formula used in this study is t-test with the results of the research note that the t-count of the calculation results, it turns out that the value of t-test obtained in this research is 9.544. While the t-table value with a significant level of 5% and d.b = (N-1) = 20-1 = 19 is 2.093. This fact indicates that the t-test value obtained in this study is greater than the t-table value. So it can be drawn a conclusion that: there is the effect of training circuit training on increasing vo2max on football players FC Ekacita